Influence of extraction pH on the foaming, emulsification, oil‐binding and visco‐elastic properties of marama protein. (17th May 2017) - Gulzar, Muhammad; Taylor, John RN; Minnaar, Amanda
Abstract: BACKGROUND: Marama bean protein, as extracted previously at pH 8, forms a viscous, adhesive and extensible dough. To obtain a protein isolate with optimum functional properties, protein extraction under slightly acidic conditions (pH 6) was investigated. RESULTS: Two‐dimensional electrophoresis showed that pH 6 extracted marama protein lacked some basic 11S legumin polypeptides, present in pH 8 extracted protein. However, it additionally contained acidic high molecular weight polypeptides (∼180 kDa), which were disulfide crosslinked into larger proteins. pH 6 extracted marama proteins had similar emulsification properties to soy protein isolate and several times higher foaming capacity than pH 8 extracted protein, egg white and soy protein isolate. pH 6 extracted protein dough was more elastic than pH 8 extracted protein, approaching the elasticity of wheat gluten. CONCLUSION: Marama protein extracted at pH 6 has excellent food‐type functional properties, probably because it lacks some 11S polypeptides but has additional high molecular weight proteins. © 2017 Society of Chemical Industry